Identifying the teaching concerns of polytechnic english language lecturers as a means to explore their professional development requirements / Suhaily Hj. Abdullah - Abdullah, Suhaily (Institute of Graduate Studies, UiTM, 2018)
This study explores polytechnic English Language lecturers' (PELLs) teaching practice in a technical and vocational education and technical (TVET) higher learning institution. It is meant to investigate PELLs' common teaching concerns in order to address their professional development. With regards to this, the combination of selected aspects and procedures from Richards and Lockhart's (1996) Reflective Teaching in Second Language Classrooms, and selected principles and concepts from Larsen-Freeman and Anderson's (2011) Principles in Language Teaching, and Wallace's (1991) Reflective Model has been used to underpin this inquiry. It is a qualitative research. The case study design was employed to investigate the PELLs' teaching practice. Six PELLs from Politeknik Cemerlang who volunteered to be involved in the project were considered as a purposeful sample and were the research participants in this study. Data were collected through informal semistructured interviews, teaching journal writing and non-participatory classroom observations. The data was manually analysed by relying on content analysis methods. The modified versions of open, axial, and selective coding were applied in obtaining the results. The study found that there are five common teaching concerns shared by the participants: concerns about pedagogical aspects, concerns about self, concerns about institutional matters, concerns about learners, and concerns about teachers' roles. These shared concerns were derived from four sources of teachers' belief which included experience as a second language learner, personality factors, established practice and institutional practice. This study also confirmed that reflective teaching procedures provided a valuable means of gaining insightful information on PELLs' teaching concerns, and it helped the researcher to relate to PELLs' professional development. Generally, PELLs are considered as effective language educators because their responses revealed that their professional knowledge consisted of four components of knowledge base required in language teaching namely: 1) knowledge about pedagogical content, 2) knowledge about learners, 3) knowledge about self, and 4) knowledge about institutional matters. However, it is suggested that specific formal inputs to improve their pedagogical content knowledge in English as Specific Purposes (ESP) teaching and to enhance their reflective teaching skills as a self-monitoring means for their own professional development should be acknowledged and prioritized to avoid lowr reticence among them. Hence, some suggestions were made to assist the professional development requirement needed by PELLs as language educators in a TVET higher learning institution. The recommendations for future studies were included to anticipate further investigations related to this particular concern.